Psychiatric comorbidity and Healthcare Effectiveness Data and Information Set (HEDIS) measures of alcohol and other drug treatment initiation and engagement across 7 health care systems. Issue 3 (3rd July 2019) - Loree, Amy M.; Yeh, Hsueh-Han; Satre, Derek D.; Kline-Simon, Andrea H.; Yarborough, Bobbi Jo H.; Haller, Irina V.; Campbell, Cynthia I.; Lapham, Gwen T.; Hechter, Rulin C.; Binswanger, Ingrid A.; Weisner, Constance; Ahmedani, Brian K.
Abstract: Background: Psychiatric comorbidity is common among patients with alcohol and other drug (AOD) use disorders. To better understand how psychiatric comorbidity influences AOD treatment access in health care systems, the present study examined treatment initiation and engagement among a large, diverse sample of patients with comorbid psychiatric and AOD use disorders. Methods: This study utilized data from a multisite observational study examining Healthcare Effectiveness Data and Information Set (HEDIS) measures of initiation and engagement in treatment (IET) among patients with AOD use disorders from 7 health care systems. Participants were aged 18 or older with at least 1 AOD index diagnosis between October 1, 2014, and August 15, 2015. Data elements extracted from electronic health records and insurance claims data included patient demographic characteristics, ICD-9 (International Classification of Diseases, Ninth Revision) diagnostic codes, and procedure codes. Descriptive analyses and multivariate logistic regression models were used to examine the relationship between patient-level factors and IET measures. Results: Across health care systems, out of a total of 86, 565 patients who had at least 1 AOD index diagnosis during the study period, 66.2% ( n  = 57, 335) patients also had a comorbid psychiatric disorder. Among patients with a comorbid psychiatric disorder, 34.9% ( n  = 19, 998) initiated AOD treatment, and of those, 10.3% ( n  = 2, 060) engaged in treatment. After adjusting for age, sex, and race/ethnicity, patients with comorbid psychiatric disorders were more likely to initiate (odds ratio [OR] = 3.20, 95% confidence interval [CI] = 3.08, 3.32) but no more likely to engage (OR = 0.56, 95% CI = 0.51, 0.61) in AOD treatment, compared with those without a comorbid psychiatric disorder. Conclusions: Findings suggest that identification of comorbid psychiatric disorders may increase initiation in AOD treatment. However, innovative efforts are needed to enhance treatment engagement both generally and especially for individuals without diagnosed psychiatric conditions.